SPESIFIKASI BENTENG-BENTENG DI KAWASAN BENGKULU PADA MASA KOLONIAL INGGRIS - Mujib (BRIN, 1995)
This paper will describe the specifications (specificity, peculiarities of the forts in Bengkulu such as the shape, location, elements, functions and roles) of the forts in the Bengkulu Region. The discussion is based on data obtained through literature and research reports on several fort sites in the Bengkulu area. The data obtained is then processed by comparing the data found in each fortress under study, analyzing the elements of the similarities and differences, then concluding and proving them through a series of information.